Implementation of Behavioral Health Protocol in the Election of Regional Head of Surakarta City during the Covid-19 Pandemic - Ida Untari; Purwanti Purwanti (Peneliti Teknologi Teknik Indonesia, 2022)
The Covid-19 pandemic that is taking place around the world has changed the order of social life. Not only the health sector, but the field of government order is also affected due to the Covid-19 pandemic. Amid concerns over the transmission of Covid-19 through crowds, the government's agenda for holding regional head elections (Pilkada) is still being held with strict requirements, one of which is the mandatory behavior of health protocols for voters, voting groups (KPPS) and witnesses from various parties involved. The government cooperates with several health professional organizations, one of which is the Indonesian Public Health Association (IPHA) as health protocol monitoring officers at several polling stations (TPS). The results of monitoring the Health protocol in the Surakarta City Election were carried out smoothly and orderly, but there were still violations of health protocols at several polling stations where KPPS officers wore masks incorrectly. This shows that there is still a need to increase awareness and assistance in implementing health protocols for several KPPS officers, as well as being an evaluation note for both the City Government and the Surakarta City Health Officeand the professional organizations on duty.